The Impact of Creativity, Market Orientation, and Competitive Strategy on Startup Performance - Susi Arijanti; Tukkot Hamonangan Immanuel; Noorhani Dyani Laksmi; Muh Zulkifli Tahir (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the impact of creativity, market orientation, and competitive strategy on startup performance. In an increasingly dynamic and competitive business environment, startups are required to leverage internal capabilities and external market insights to achieve sustainable growth. This research adopts a quantitative approach using a cross-sectional survey design, with data collected from 187 startup founders and managers in Indonesia through structured questionnaires. The data were analyzed using multiple linear regression analysis to test the proposed hypotheses. The results indicate that creativity, market orientation, and competitive strategy each have a positive and significant effect on startup performance. Among these variables, creativity emerges as the most influential factor, highlighting the importance of innovation and idea generation in enhancing business outcomes. Furthermore, the findings reveal that the three variables simultaneously contribute significantly to startup performance, suggesting that an integrated approach is essential for achieving optimal results. This study provides both theoretical and practical contributions by emphasizing the need for startups to align creative capabilities with market understanding and strategic positioning. The findings offer valuable insights for entrepreneurs and managers in developing effective strategies to improve performance and ensure long-term sustainability.